(untitled) (Letters in Nonlinear Analysis and its Applications, 2025)
Recently we obtained several extensions of the Banach contraction principle. One of them is the weak contraction principle or the Rus-Hicks-Rhoades contraction principle or Theorem P. There are a large number of examples or applications of Theorem P in the literature. Recently, Romaguera stated two corollaries of Theorem P are false. Our main aim of this paper is to clarify his claim